Urachal abnormalities in the adult population. Is physical activity involved in clinical manifestation Literature review - Męczyńska, Joanna; Mazurkiewicz, Aleksandra; Mądry, Wojciech; Marcicka, Justyna; Kołodziej, Magdalena; Saiuk, Nazarii; Wojciechowska, Adriana; Seredyński, Tomasz; Kozicz, Michał Andrzej; Salasa, Weronika (Quality in Sport, 2024)
Introduction The urachal anomaly is a developmental defect, a remnant of fetal life consisting of a patent connection between the dome of the urinary bladder and the umbilicus. It can take various forms. Most commonly it occurs in males, very rarely in adults. The main symptoms associated with this condition are: foul-smelling discharge from the umbilicus, abdominal pain, hematuria, or recurrent urinary tract infections. Imaging plays a crucial role in the diagnosis of the persistent urachus. Aim of the study The aim of the study is to sentize doctors’ attention that patent urachus is the rare but possible diagnosis of acute abdomen pain in adults population and bring the proceedings. Materials and methods: An analysis of papers avaliable on Pubmed and Google Scholar was performed. The following key words: urachal anomalies, adults, abdomen pain, urachal remnants, urachal carcinoma were used. Results: Lately, thanks to modern precise imaging diagnostics, more valuable studies have been conducted, allowing to characterize residual ureteral remnants, which are most often asymptomatic in population of adults. However the manifestation of symptoms is mostly associated with infection of the mentioned area or a tumor transformation. There are at least two case reports which report that infection of urachal remnants could manifestate after intensive physical activity. It is worth in-depth interviewing. Studies indicate the necessity of surgical removal of persistent urachal anomalies, as they carry the risk of rapid growth and unfavorable prognosis of cancerous spread.